1999
DOI: 10.1007/s004380050948
|View full text |Cite
|
Sign up to set email alerts
|

T-DNA from Agrobacterium tumefaciens as an efficient tool for gene targeting in Kluyveromyces lactis

Abstract: The soil bacterium Agrobacterium tumefaciens can transfer a part of its tumour-inducing (Ti) plasmid, the T-DNA, to plant cells. The virulence (vir) genes, also located on the Ti plasmid, encode proteins involved in the transport of T-DNA into the plant cell. Once in the plant nucleus, T-DNA is able to integrate into the plant genome by an illegitimate recombination mechanism. The host range of A. tumefaciens is not restricted to plant species. A. tumefaciens is also able to transfer T-DNA to the yeast Sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…None of these contained the correct Klacs2 disruption as tested by Southern analysis or PCR. Even the use of Agrobacterium tumefaciens for conjugation with K. lactis GG1916, which reportedly increases homologous recombination in K. lactis (Bundock et al , 1999), was unsuccessful. Eventually, transformation with the entire subcloned 7 kb Sph I fragment resulted in proper integration, although it took 3 weeks for the primary transformants to form sizeable colonies.…”
Section: Resultsmentioning
confidence: 99%
“…None of these contained the correct Klacs2 disruption as tested by Southern analysis or PCR. Even the use of Agrobacterium tumefaciens for conjugation with K. lactis GG1916, which reportedly increases homologous recombination in K. lactis (Bundock et al , 1999), was unsuccessful. Eventually, transformation with the entire subcloned 7 kb Sph I fragment resulted in proper integration, although it took 3 weeks for the primary transformants to form sizeable colonies.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the T‐DNA derived plasmids that could be recovered provide ample evidence to support the proposed model. Besides that, the model is corroborated by the fact that integrated T‐DNA multimers have been recovered from the yeast strain Kluyveromyces lactis after AMT (Bundock et al ., ). Furthermore, earlier research on conjugal plasmids provided evidence for site‐specific recombination at the oriT sequence both within and between plasmids (Warren and Clark, ; Llosa et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Co‐cultivations between A. tumefaciens strain LBA1126 (pRAL7207) and RSY12 (Schiestl et al ., 1991) were carried out as previously described (Bundock et al ., 1999). The co‐cultivations between LBA1119 (pSDM8000) and YPH250 (Sikorski and Hieter, 1989) were performed in a slightly different way.…”
Section: Methodsmentioning
confidence: 99%
“…T‐DNA can therefore be used as a gene vector for these organisms, which is most relevant for species that cannot be otherwise efficiently transformed. In the absence of homology the T‐DNA integrates into the yeast chromosomal DNA by non‐homologous recombination (NHR) (Bundock et al ., 1995, 1999; Bundock and Hooykaas, 1996; De Groot et al ., 1999). This suggested that the T‐DNA could be used as an effective insertional mutagen for yeasts and fungi.…”
Section: Introductionmentioning
confidence: 99%